Impact of Ticagrelor vs. Clopidogrel in Patients With Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention After Risk Stratification With the CHA2DS2-VASc Score - Na, Kun; Qiu, Miaohan; Ma, Sicong; Li, Yi; Li, Jing; Liu, Rong; Zhang, Jiaoyang; Han, Yaling (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: The clinical benefit of ticagrelor versus clopidogrel in unselected patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI) remains controversial in the real world. This study was aimed to investigate the impact of ticagrelor vs clopidogrel in subjects with ACS after PCI based on risk stratification using the CHA2DS2-VASc score. Methods: In 2016–2019, patients who underwent PCI with at least one stent implanted in the General Hospital of Northern Theater Command were classified as low-risk or high-risk groups according to the CHA2DS2-VASc score. Incidences of 12-month ischemia (cardiac death, myocardial infarction (MI) or stroke), all-cause death, Bleeding Academic Research Consortium (BARC) 2,3,5 bleeding BARC 3,5 bleeding and NACEs (all-cause death, MI, stroke or BARC 3, 5 bleeding), with aspirin plus different P2Y12 inhibitors (clopidogrel or ticagrelor) were appraised among different risk groups. Propensity score matching (PSM) and Cox multivariate analysis were used to balance groups. Results: A total of consecutive 17,037 ACS patients were enrolled. The optimal cut-off value of CHA2DS2-VASc score for ischemic events by the Youden test was 3 points. Among patients with high risk (CHA2DS2-VASc≥3, n=6151), ticagrelor was associated with lower risks of ischemic events (2.29% vs 3.54%, P=0.02), stroke (0.39% vs 1.08%, P=0.01) without excessive risk of BARC 3,5 bleeding events (2.16% vs 2.11%, P=0.92) compared to clopidogrel within 12 months after PCI. For patients with low risk (CHA2DS2-VASc <3, n=10886), a statistically significant difference was seen in the incidence of overall 12-month BARC 2, 3, 5 bleeding events by P2Y12 receptor inhibitor (4.00% vs 3.26%) with a similar incidence of the ischemic events (1.40% vs 1.52%). Results in the PSM cohort and the adjustment with Cox multivariate analysis were consistent with the main outcomes. Conclusion: Higher CHA2DS2-VASc scores were associated with higher incidence of 1-year ischemic events for the ACS patients after PCI. Compared with clopidogrel, ticagrelor was associated with lower ischemic events within 12 months after PCI without excessive risk of bleeding in high-risk patients but shows worse safety with bleeding excess in low-risk patients.